Volumes of Velopharyngeal and Glossopharyngeal Airway Were Not Changed after Uvulopalatopharyngoplasty: Report of Three Cases. (24th March 2016) - Nishimura, Yoichi; Fujii, Naoko; Yamamoto, Takahisa; Hamed, Mahmood A.; Nishimura, Misato; Kojima, Takuro; Iwata, Noboru; Suzuki, Kenji; Nakata, Seiichi
Abstract : Objective . The aim of this study was to investigate the changes in velopharyngeal and glossopharyngeal airway morphology and volume after uvulopalatopharyngoplasty in three adult obstructive sleep apnea syndrome patients who had bilateral large tonsils using three-dimensional computed tomography. Case Report . All three patients (one male and two females) who presented with a history of heavy snoring and excessive daytime sleepiness were examined with overnight nocturnal polysomnography, which indicated moderate-to-severe obstructive sleep apnea syndrome. Because all patients had large tonsils, uvulopalatopharyngoplasty was expected to enlarge the pharyngeal airway. Polysomnography and three-dimensional computed tomography scanning were performed and compared, both before and 3 months after uvulopalatopharyngoplasty. Results . Unexpectedly, although the morphology of the glossopharyngeal airway clearly changed after UPPP, the volume changes in the velopharyngeal and glossopharyngeal airways were negligible.